MANAJEMEN ARSIP PERGURUAN TINGGI DI ERA NEW PUBLIC SERVICE (SEBUAH PEMIKIRAN UNTUK ARSIP PERGURUAN TINGGI UNIVERSITAS DIPONEGORO): Array - Tri Handayani (Jurnal Kearsipan, 2010)
Traditionally, universities are assigned three missions: to teach, conduct research, and provide public service. Records created resulting the assignment should be managed systematically in a university archives system from the creation to disposal, and then continue being retained at the next phase, namely archives. The University archives, as institutions holding all archives management functions, has to develop filling and archives management system. Research problem of this writing is to study on how the universities implement records management activities in the new public service era. The research was conducted in adescriptive format. It is aimed to outline general concept of archives management through literature study. The study is to compare record management units, namely, first archival unit and second archival unit, and to review the results of the third-time preparation of Diponegoro University Archives establishment by a research team from Archival Diploma Program of Faculty of Humanities at University of Diponegoro. Direct observation was done in some work units at University of Diponegoro as study samples. The purpose is to seek arising problems and inhibiting problems concerning records and archives management in colleges. Interviews conducted both in a structured and unstructured with record managers and archivists at University of Diponegoro as well as other potential users at the university archives. The goal was to find out policies on direct applicably record management and its implementation. The study was to support the implementation of the Act Number 43 of 2009 which says ‘universities can organize information service file based system to the maximum to its users’. The research recommended, as the pioneer in developing national archival intensive communication with related ministries, other institutions as well as high education institutions, National Archives of the Republic of Indonesia must have built synergies among those institutions in order to obtain one perception on university archives functions. If the synergy had been acquired then the weakness would have been resolved.